Conflict in protected areas: who says co-management does not work? - Pourcq, K. de; Thomas, E.; Arts, Bas; Vranckx, A.; León Sicard, T.; Damme, Patrick van (Public Library of Science, 2015)
Natural resource-related conflicts can be extremely destructive and undermine environmental protection. Since the 1990s co-management schemes, whereby the management of resources is shared by public and/or private sector stakeholders, have been a main strategy for reducing these conflicts worldwide. Despite initial high hopes, in recent years co-management has been perceived as falling short of expectations. However, systematic assessments of its role in conflict prevention or mitigation are non-existent. Interviews with 584 residents from ten protected areas in Colombia revealed that co-management can be successful in reducing conflict at grassroots level, as long as some critical enabling conditions, such as effective participation in the co-management process, are fulfilled not only on paper but also by praxis. We hope these findings will re-incentivize global efforts to make co-management work in protected areas and other common pool resource contexts, such as fisheries, agriculture, forestry and water management.